Meningkatkan Kinerja Operasional Melalui Strategi Penugasan Karyawan Yang Efisien - Melsandi, Sindi Dwi; Martini, Nelly (Peneliti.net, 2025)
In the era of globalisation, companies in various industrial sectors pursue high efficiency and productivity through optimising operational performance, one of which is through efficient employee assignment strategies. Employees are key assets that determine the success of the company with their unique contributions that cannot be equated with machines or materials. Employees' abilities and skills affect the quality of work, so companies need to maintain and manage their performance well. Strategies to improve performance include providing rewards, incentives, and proper training to motivate employees, which contributes to achieving company goals and creating a productive work culture. This research uses a qualitative approach with the Grounded Theory method to describe the research focus. The result of this research is that the strategy of improving employee performance aims to improve the quality and results of employee work through several effective methods, such as work meetings for evaluation and communication, job training that improves skills and knowledge, and providing motivation through rewards and incentives. Work meetings allow employees to review performance, find solutions and make decisions together, while on-the-job training helps them work more efficiently and accurately. Motivation and rewards encourage employee morale, creativity and productivity, and attract and retain employees.